Performance simulation of a two-phase flow distributor for plate-fin heat exchanger. (25th April 2016) - Yuan, P.; Jiang, G.B.; He, Y.L.; Tao, W.Q.
Highlights: A novel structure of gas–liquid distributor is numerically investigated. The results show that the relative flow ratios are usually in the rage of 0.7–1.3. The gas side smallest maldistribution is reached when liquid volume fraction is 60‰. Graphical Abstract: Abstract: Uniform distribution of two-phase flow mixture at the inlet of the plate-fin heat exchanger is critical to the high performance of heat exchanger. Special distributors are often used to improve the distribution. The major purpose of the present paper is to numerically study the distribution characteristics of one type of distributor by using the commercial software CFX. The major feature of this distributor is that ahead of the distributor, gas and liquid separately go into the distributor. Simulations are conducted for air–water mixture. The results reveal that compared with conventional distributors in which ahead of the distributor the fluid is already a two-phase mixture, the proposed distributor can appreciably improve the flow distribution of the plate-fin heat exchanger.